Analisis Dampak Subsidi Listrik terhadap Kesejahteraan Rumah Tangga Berpendapatan Rendah - Wulan Purnamasari; Ika Wisudawaty (Micronic: Journal of Multidisciplinary Electrical and Electronics Engineering, 2025)
Electricity subsidy is one of the government intervention policies in order to improve people's welfare, especially low-income households. This study aims to analyze the impact of electricity subsidies on household welfare in terms of expenditure, access to children's education, and economic productivity. This study uses a quantitative approach with a survey method of 120 households receiving subsidies in urban and rural areas in South Sulawesi Province. The results of the study indicate that electricity subsidies are able to reduce the proportion of electricity expenditure to total household expenditure, increase children's attendance and learning activities at night, and encourage household economic activities such as micro and home businesses. Thus, electricity subsidies have been proven to make a positive contribution to improving welfare, although improvements are still needed in the beneficiary targeting system. This study recommends increasing the accuracy of subsidy recipient data and integrating programs with household productivity interventions.